Oral Delivery of Bacillus subtilis Expressing Chicken NK-2 Peptide Protects Against Eimeria acervulina Infection in Broiler Chickens - Wickramasuriya, Samiru S.; Park, Inkyung; Lee, Youngsub; Kim, Woo H.; Przybyszewski, Chris; Gay, Cyril G.; Oosterwijk, Jolieke G. van; Lillehoj, Hyun S. (Frontiers in Veterinary Science, 2021)
Chicken NK-lysin peptide 2 (cNK-2) is a natural lytic peptide with direct cytotoxicity against many apicomplexan parasites including Eimeria. Developing an effective oral delivery strategy to express cNK-2 in the intestine where Eimeria parasites interact with the host’s gut epithelial cells, may effectively reduce the fecundity of parasites and minimize intestinal damage. Furthermore, cNK-2 modulates gut immune responses to decrease local inflammation elicited by Eimeria infection in the intestine. Therefore, we developed a stable strain of Bacillus subtilis (B. subtilis) that carries cNK-2 to the gut to determine its effectiveness in ameliorating the negative impacts of coccidiosis and to replace the use of antibiotics in controlling coccidiosis in commercial broiler chicken production. Chickens were randomly allocated into eight treatment groups: two control groups (NC: E. acervulina infected non-B. subtilis control; CON: non-infected control); three B. subtilis-empty vector (EV) groups (EV6: 106 cfu/day/bird; EV8: 108 cfu/day/bird; EV10: 1010 cfu/day/bird), and three B. subtilis-cNK-2 groups (NK6: 106 cfu/day/bird; NK8: 108 cfu/day/bird; NK10: 1010 cfu/day/bird). All chickens, except those in the CON group, were challenged with 5,000 freshly sporulated E. acervulina oocysts through oral gavage on day 15. Chickens were given an oral dose of B. subtilis on days 14, 15, and 16. Body weight, weight gains, and fecal oocyst shedding were measured. To investigate the efficacy of oral B. subtilis-cNK-2 against coccidiosis, gene expression of gut health-related biomarkers was measured using RT-PCR. Markers included SOD1, CAT, and HMOX1 for oxidative stress in the spleen and intestinal mucosa, OCLN, ZO-1, and JAM2 for tight junction proteins, and MUC2 for mucin gene expression in the gut. The results showed that oral treatment of young chickens with B. subtilis-cNK-2 improved growth performance, enhanced gut integrity, and reduced fecal oocyst shedding. Altogether, these results confirm B. subtilis-cNK-2 treatment as a promising and effective alternative strategy to replace antibiotics against coccidiosis based on its ability to reduce parasite survival; to reduce coccidiosis-induced body weight loss; to decrease gut damage based on the enhanced expression of proteins associated with gut integrity and intestinal health.